Estimasi Volume Sedimentasi Waduk Sermo Menggunakan Metode RUSLE, Batimetri dan Angkutan Sedimen - Annisa Wulandari; Bambang Kun Cahyono (Jurnal Geospasial Indonesia, 2020)
Sermo Reservoir is a reservoir which was built by Indonesian Government and supported by Asian Development Bank in program Integrated Irrigation Sector Project (IISP) in 1996. Sermo Reservoir functions as a flood control, raw water source and irrigation. Changes that occur to water catchment area of the Sermo Reservoir affects its condition. Especially changes that occur in aspects of water runoff, sediment production and watershed deposition of watershed aspects which are caused by erosion in water catchment area resulting in sedimentation. Long term sedimentation causes a decrease in reservoir capacity. To overcome this problem it is necessary to estimate the sedimentation volume to determine the latest condition of the Sermo Reservoir. In this activity, volume estimation of sedimentation was conducted using RUSLE, bathymetry and sediment transport methods. The data used in this activity are the data in 2016, 2017 and 2018. In this activity, the analysis of the RUSLE method in the Ngrancah Watershed includes the factors of rainfall erosivity, soil erodibility, length and slope and land cover and preservation. In addition to RUSLE, an analysis was carried out using the bathymetry method. This method calculates sedimentation based on reservoir baseline DTM data of 2017 and 2018. From the difference between both DTM epochs, obtained sediment volume and spread of Sermo Reservoir. Besides, analysis of the sediment transport method was conducted using water soil content data of 2016 which is assumed static until 2018. While analyzing with RUSLE, bathymetry and sediment transport methods using ArcGIS Software. The results of volume estimation of sedimentation using RUSLE, sediment transport and bathymetry consecutively yields 184.158,580 m3/year, 163.151,173 m3/year and 149.959,800 m3/year. Thus the estimation results of sediment thickness velocity of Sermo Reservoir using RUSLE, bathymetry and sediment transport are 8,687 mm/year, 7,790 mm/year and 7,074 mm/year. Generated volume from the methods was tested by using precision test yielding RSD 8,407 % thus classified as low accuracy. From the precision test can be concluded that sediment transport was the most precise because it has a percentage difference of -0,766 % of the average sediment volume.